Cinema hollywoodiano no século XXI: o ritmo em abordagem semiótica e os filmes mais vistos de 2001 a 2010 - Merenciano, Levi Henrique [UNESP] (2015)
Both box office success and possible disaffection of canonical criticism, in fact, the Hollywoodian cinema is a theme not too attractive in Brazilian academic theses. In the surroundings of this relationship - sometimes contractual, sometimes controversy (since they involve different opinions amongst public, critics and art) - it is necessary to describe the semiotics strategies within the meaning processes inherent to the movies, in order to explain, by means semiotics visual processes theory, the organization of expression rhythms and content rhythms that contemporary Hollywood films are able to manifest. In explaining the organization of plane of content and plane of expression of the most viewed films on the first decade of this century it is possible to defend hypotheses on different types of film structure, as the incidence of paratactic and hypotactic rhythms (with predominantly syntagmatic or paradigmatic effects), which aspect can be continuous or discontinuous. These concepts have a starting point on the structuralism (Saussure, Roman Jakobson, Christian Metz) and an arrival point on discursive semiotics (Algirdas J. Greimas and Courtes Joseph), also on the plastic approach (Jean-Marie Floch ) and on the studies of rhythm (Louis Hébert). The corpus is organized from the most viewed films in the last decade, from 2001 to 2010 (according to Box Office Mojo website). A set of significant units (the relevant sequences) four most watched movies will be analized: James Cameron's Avatar (2009), Gore Verbinski's Pirates of the Caribbean (2006), Lee Unkrich's Toy Story 3 (2010) and Peter Jackson's Lord of the Rings (2003). In order to describe the processes of meaning in film language, semiotic principles will be established to help observe and analize the relevant structural and resemblances in the movies mentioned (when possible, comparing them to other visual and verbal visual objects), to indicate differences and ...